Government and politics in the Nordic countries: Denmark, Finland, Iceland, Norway, Sweden - Andren, Nils Bertel Einar, 1918- (Stockholm : Almqvist & Wiksell, 1964)
Written primarily for foreign students of government at the Institute for English Speaking Studies of the University of Stockholm.
'Bibliography' : pages 234-236.
Keywords: Constitutional history -- Scandinavia; Constitutional history -- Finland; Constitutional history -- Iceland